АНАЛІЗ ІМПЕДАНСНОЇ МОДЕЛІ ДВОЕЛЕКТРОДНОЇ КОНТАКТНОЇ КОНДУКТОМЕТРИЧНОЇ КОМІРКИ - Михаль, А.А.; Мелещук, Д.В. (Інститут електродинаміки НАН України, Київ, 2020)
The results of the study of the electric model of a two-electrode conductometric cell when measuring with alternating current are presented. The proposed model is based on the series connection of two impedances, which describe the near-electrode processes and processes in the volume of the test solution. It allows you to separately evaluate the informative and non-informative parameters of equivalent replacement schemes. The results of a theoretical study of the frequency properties of the near-electrode and volume impedances are presented. Based on them, simplifications of the equivalent cell impedance substitution scheme for the frequency-measuring subbands are proposed. The results of the study of the components of the cell impedance are given. A number of parameters have been determined that allow an experimental assessment of the legitimacy of the application of the electric cell model. References 30, figures 5.